Seasons in Italy: Northern European travelers, Rome, and malaria. Issue 1 (2nd January 2021) - Reilly, Benjamin
ABSTRACT: The city of Rome has long been one of the most visited cities in Europe, but such visits were historically a risky proposition due to Rome's resident P. vivax and P. falciparum malaria. As a result, many French and English travel guides cautioned against visiting Rome during the summer, when Rome's 'bad air' could prove fatal to travelers. But to what degree was this advice actually followed? To answer this question, this paper examines the itineraries of 271 travelers to Italy from 1400 to 1850, looking in particular at two main data points: 1) the seasonality of their travel patterns within Italy, and 2) the knowledge these travelers exhibited about malaria, feverish seasons and landscapes, or unhealthy air. In the end, this paper concludes that northern European travel to Italy was highly seasonal, and that the desire to be out of Rome during the dangerous summer season left an marked imprint on visiting patterns in Rome and other Italian cities. In addition, it appears that this pattern of avoiding the Roman summers was not merely a matter of comfort, but correlated strongly with explicit knowledge of Rome's summer malarial risks.